MOLECULAR APPROACH TO DETERMINE THE HOT AND COLD TEMPERAMENTS IN PLANTS ACCORDING AVICENNA CONCEPTS, THE ROLE OF MAGNESIUM - M. SHAROFOVA; I. ALDYBIAT; SH. SAGDIEVA; YU. NURALIEV; F. RAHIMI; M. MIRSHAHI (Avicenna Tajik State Medical University, 2018)
Objective: The molecular approach of millenary notion about hot and cold temperaments (mizaj) in plants according to Avicenna concepts is not investigated. The aim of this study is to analyze the correlation between mizaj property of plants from the Tajikistan area and their amount/quality of metal. Methods: We analyzed the presence of several metals that implicated in body's homeostasis integrity, such as sodium, potassium, calcium, and magnesium, in several edible plants (n=23) from different regions in Tajikistan. Samples (n=43) of plant's parts including seeds, flower, leaf, stem and root were analyzed for their elements' composition using Energy Dispersive X-Ray Analysis (EDX) which incorporates Scanning Electron Microscopy (SEM). Results: We didn't find any correlation between the area of the collected samples and the amount of metal absorbance by the plants. The metals distributions of plant's parts varied from one to the other. In this study, we found strict correlation between the amount of magnesium and the temperament properties of the plants reported by Avicenna. The magnesium was detected in high amount in Achillea millefolium L., Rosa canina L., Coriandrum sativum L., Foeniculum vulgare Mill. and Nigella sativa L. Conclusion: The presence of high concentration of magnesium in the edible plants can be considered as a metal contribution (factor) in hot mizaj property and may lead to energy regeneration and wellbeing after consumption.